Investigation and experimental verification of untethered microrobot motion behavior subject to laminar flow - Demirçalı, Ali Anıl (My University, 2021)
Untethered manipulation of microrobots is emerging as a promising field of research in medical and biological applications. This study presents an untethered micromanipulation technique to control magnetic microrobot with high precision positional accuracy inside a microfluidic channel. It is aimed to develop an untethered microrobotic platform that can operate on high flow rate microfluidic channels for in vitro applications. Firstly, a novel diamagnetic untethered levitation configuration is used in order to eliminate the friction force between the substrate’s surface and the microrobot. Secondly, the drag force acting on the microrobot is decreased to move microrobot longitudinally towards and against the flow. After that, the liquid media’s hydrodynamic effects on microrobot is optimized by finite element method (FEM) simulations in COMSOLR (version 5.3, COMSOL Inc., Stockholm, Sweden). Analytical and simulation studies are conducted, which are then validated by experimental results to demonstrate the advantages of the developed platform. Experimental results are on par with analytical and simulation studies and this platform significantly improves the longitudinal forces on the microrobot. Moreover, it also provides a more stable lateral motion in fluidic channels where a high rate flow is present. An increase in flow rate exponentially increases the drag force on the microrobot and negatively impacts its positioning accuracy. Increasing the longitudinal force generated by the microrobot’s driving apparatus helps disrupt the fluid flow and increases longitudinal motion stability. No prior study exists that investigates the longitudinal motion of a microrobot for high flow velocities (>∼ 5mm/s). Longitudinal force investigation is an important topic for increasing the applicability of microrobots in many areas such as cell research, micromanipulation, and lab-on-a-chips. The following points are achieved in the relevant study and their details are given: - The microrobot can move in three dimensions and two orientations in a liquid environment. - The microrobot stable levitation range is determined between 30 µm to 330 µm. This range is also confirmed with simulation and experimental studies. Furthermore, the microrobot capable of tracking desired trajectory with the accuracy of <1 µm at varying speed. Also, the levitation height can be adjusted in the stable working range. - Rule-based, laser-feedback, visual-feedback, and hybrid model controllers are designed for reducing the microrobot orientation at higher speeds. - Demonstration the ability of a microrobot in a square-shaped microfluidic channel follow a linear trajectory with a relative flow velocity up to 132.6 mm/s.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Microrobot motion; Motion in flow; Diamagnetic levitation; Reynolds number; Laminar flow